Acceptability of multiple micronutrient powders and iron syrup in Bihar, India - Young, Melissa F.; Girard, Amy Webb; Mehta, Rushkan; Srikantiah, Sridhar; Gosdin, Lucas; Menon, Purnima; Ramakrishnan, Usha; Martorell, Reynaldo; Avula, Rasmi (Wiley, 2018)
Nearly two thirds of young children are anaemic in Bihar, India. Paediatric iron and folic acid syrup (IFAS) and multiple micronutrient powders (MNPs) are two evidence-based interventions to prevent anaemia. Using a randomized crossover design, we examined the acceptability of IFAS versus MNPs for children 6–23 months. In a catchment area of 2 health centres in Bihar, health front-line workers (FLWs) delivered either (a) IFAS twice weekly or (b) MNPs for 1 month followed by the other supplementation strategy for 1 month to the same families (NCT02610881). Household surveys were conducted at baseline (N = 100), 1 month after receiving the first intervention (1 month; N = 95), and 1 month after the second intervention (2 months; N = 93). Focus group discussions (10 FLWs) and in-depth interviews (20 mothers) were held at 1 and 2 months. We used chi-square and Fisher exact tests to test mothers' product preferences. Qualitative data were analysed using MaxQDA and Excel employing a thematic analysis approach. There was high adherence and acceptability for both products (>80%). There was no significant difference in preference (p < .05) on perceived benefits (39% MNPs, 40% IFAS), side effects (30% MNPs, 30% IFAS), ease of use (42% IFAS, 31% MNPs), child preference (45% IFAS, 37% MNPs), and maternal preference (44% IFAS, 34% MNPs). Mothers and FLWs indicated that the direct administration of IFAS ensured that children consumed the full dose, and MNPs intake depended on the quantity of food consumed, especially among younger children, which emphasizes the need to integrate supplementation with the promotion of optimal child feeding practices.